1997
DOI: 10.1103/physrevb.56.3276
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-well-induced ferromagnetism in thin films

Abstract: We have used a first-principles Green's-function technique to investigate the magnetic properties of thin films of Rh, Pd, and Pt deposited on a fcc Ag ͑001͒ substrate. We find that the magnetic moment of the film is periodically suppressed and enhanced as a function of film thickness. The phenomenon is explained in terms of quantum-well states moving through the Fermi level with increasing film thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 25 publications
5
39
1
Order By: Relevance
“…We use this technique to probe two Sc-C 60 and Cu-C 60 samples whose structure includes a thin Sc film of 2 nm (2.5 nm for Cu-C 60 ) and a thick Sc film of 5 nm (15 nm for Cu-C 60 ). Nanoscaling of nonmagnetic metals has been shown to give rise to spin ordering (30)(31)(32)(33). The thin films should give rise to a strong magnetic signal, whereas for the thicker films, the interfacial magnetization should be quenched or diluted by the bulk properties of the metal.…”
Section: Systemmentioning
confidence: 99%
“…We use this technique to probe two Sc-C 60 and Cu-C 60 samples whose structure includes a thin Sc film of 2 nm (2.5 nm for Cu-C 60 ) and a thick Sc film of 5 nm (15 nm for Cu-C 60 ). Nanoscaling of nonmagnetic metals has been shown to give rise to spin ordering (30)(31)(32)(33). The thin films should give rise to a strong magnetic signal, whereas for the thicker films, the interfacial magnetization should be quenched or diluted by the bulk properties of the metal.…”
Section: Systemmentioning
confidence: 99%
“…Here, most of the systems examined have been Rh adlayers on noble metal substrates. Theoretical predictions have suggested that single Rh MLs will be magnetic on Ag (111) [16,17] and (001) [13,16,[18][19][20][21][22][23][24], Au (111) [16] and (001) [13,16,23,25], Ni (111) [26] and Cu (001) [16,[27][28][29] but non-magnetic on Ag (110) [16], Au (110) [16], Cu (110) [16] and Cu (111) [16]. In the magnetic cases, the moments are predicted to decrease rapidly with increasing numbers of Rh layers, usually becoming very weak by film thicknesses of just 2 ML [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…The discussion is close to previous work 35 where it was shown how multiple-scattering effects such as quantum-well states only give a small, almost constant, contribution to the magnetic profile in Fe/Cu/Fe trilayers. Multiple-scattering effects can sometimes be important for the magnetization in thin films and may even induce an onset of magnetism in paramagnetic materials 36 or quench the magnetism in ferromagnetic materials. 37 However, these enhancements or quenching effects are mainly of importance for thin films of nearly magnetic materials such as Rh, Pd, and Pt.…”
Section: Magnetic Trilayersmentioning
confidence: 99%